Cutaneous Horn Overlying Lichen Simplex Chronicus - Verma Rajesh; Jaiswal A.K (Wolters Kluwer Medknow Publications, 1999)
A 40 year old man presented with cutaneous horn overlying a lichen simplex chronicus lesion on right leg of 6 years duration.